(untitled) (ETIMA, 2021)
Abstract The focus of the research study is on analyses, assessment and evaluation of the digital skills and competencies of administration and defines their proficiency levels in order to offer a solution for a better development in administrative work. Every individual is meant to have a certain level of proficiency in digital skills. However, the current education system has fallen short of providing our future generations with the basic understanding of what it takes to succeed in a digital environment. The goal of this paper is to assess the digital skills and competencies of administration and define their proficiency levels. Depending on their findings, the study suggest recommendation and ways by which universities can improve on their curriculum so that students are better equipped when they enter the workforce. Digital competency is a term used to describe the skills and knowledge required to be digitally literate. Given the widespread use of digital technologies across the administration, competencies are needed to properly drive the digital change. Technologies are increasingly complex, diverse and with a fast-paced evolution that requires governments to increase efforts to keep the skill sets of public officers updated, but also to anticipate the needs associated with emerging change. This assessment in the form of strategic digital skills from an educational viewpoint is an essential measurement of the required skills of the future workforce. Key words: Digital Skills, Assessment, Public administration proficiency, digital competences